Byproducts of orange extraction: influence of different treatments in fiber composition and physical and chemical parameters - Juliana Maria de Mello Andrade; Erna Vogt de Jong; Amélia Teresinha Henriques (Universidade de São Paulo, 2014)
In this work we evaluated the variability in fiber content and physical and chemical parameters of byproducts from orange juice extraction. Five different treatments and two drying methods were evaluated. The results indicate that drying by lyophilization was better than that drying in an oven. The pH ranged from approximately 3.47 to 3.96. The variation in moisture values was 9.22% ± 0.02 to 18.48 ± 0.52%. The total dietary fiber content in the resulting flours ranged from 42.44% to 62.74%. The soluble and insoluble dietary fiber contents differed among the samples, ranging from 5.04% to 19.95% for the first fiber type, and 23.96% to 57.70% for the second. In conclusion, three treatments, associated with freeze-drying, showed promising results in the development of fiber-rich product. However, some modifications are needed, as well as further analysis, to guarantee the benefits of these products for human health. This study contributes to the possible application of industrial byproducts.